Could Treatment Matching Patients' Beliefs About Depression Improve Outcomes?. Issue 4 (July 2019) - Vittengl, Jeffrey R.; Clark, Lee Anna; Thase, Michael E.; Jarrett, Robin B.
Abstract: Patients' beliefs about depression and expectations for treatment can influence outcomes of major depressive disorder (MDD) treatments. We hypothesized that patients with weaker biological beliefs (less endorsement of [a] biochemical causes and [b] need for medication) and more optimistic treatment expectations (greater improvement and shorter time to improvement), have better outcomes in cognitive therapy (CT). Outpatients with recurrent MDD who received acute-phase CT ( N = 152), and a subset of partial or unstable responders ( N = 51) randomized to 8 months of continuation CT or fluoxetine with clinical management, completed repeated measures of beliefs, expectations, and depression. As hypothesized, patients with weaker biological beliefs about depression, and patients who expected a shorter time to improvement, experienced greater change in depressive symptoms and more frequent response to acute-phase CT. Moreover, responders who received continuation treatment better matched to their biological beliefs (i.e., responders with weaker biological beliefs about depression who received continuation CT, or responders with stronger biological beliefs about depression who received continuation fluoxetine) had fewer depressive symptoms and less relapse/recurrence by 32 months after acute-phase CT than did responders who received mismatched continuation treatment. Specific screening and/or intervention targeting patients' biological beliefs about depression could increase CT efficacy. Highlights: Patients hold varying beliefs about their problems and treatment expectations. We studied outpatients with recurrent major depressive disorder (MDD). Biological beliefs predicted poorer outcomes in acute-phase cognitive therapy (CT). Responders with fewer biological beliefs relapsed less with continuation CT. Responders with more biological beliefs relapsed less with continuation fluoxetine.